Analisis Pendapatan Asli Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus Terhadap Pengalokasian Belanja Modal (Studi Empiris pada Pada Pemerintahan Kabupaten/Kota di Provinsi Banten Tahun 2013 -2018) - Raharjo, Wilujeng Teguh; Harnovinsah, Harnovinsah (Fakultas Ekonomi Universitas IBA, 2021)
This study examines the effect of income original Region, general allocation fund, special allocation fund on allocating capital expenditure on the districts and cities government in Banten Province. This study's populations are four districts and four cities in Banten Province that already have the reports realization region Budget and Expenditure (APBD) in the period 2013-2018, obtained from Directorate-General of Regional Fiscal Balance's official website. This study's analysis test is multiple regression. This study showed that income original region and general allocation fund positively and significantly affect capital expenditure allocation. In contrast, special allocation funds offer a negative and not significant impact on capital expenditure allocation.